Biologics to Treat Substance Use Disorders Vaccines, Monoclonal Antibodies, and Enzymes - Montoya, Ivan D. (Springer International Publishing : Imprint: Springer, 2016)
This book is a scientific compendium documenting the state of the art in the discovery and development of vaccines, monoclonal antibodies, and enzymes for the treatment of Substance Use Disorders (SUDs). The book gives detailed consideration to some of the most cutting edge topics in addiction medicine, including vaccines for nicotine, cocaine, heroin, and methamphetamine dependence; monoclonal antibodies against cocaine, methamphetamine, and phencyclidine; and the enzymes butyrylcholinesterase and cocaine esterase. In addition, the text covers a wide range of new strategies designed to optimize the development and efficacy of biologics. Unlike any other resource, this book reviews how biologics offer exciting new therapeutic opportunities for various psychiatric conditions. Written by experts in the field, Biologics to Treat Substance Use Disorders is as an authoritative reference for psychiatrists, psychologists, and all other medical professionals working with patients suffering from Substance Use Disorders.